2010
DOI: 10.1111/j.1463-1326.2010.01197.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sitagliptin monotherapy compared with voglibose in Japanese patients with type 2 diabetes: a randomized, double‐blind trial

Abstract: Objective:To compare the efficacy and safety of sitagliptin (a dipeptidyl peptidase-4 inhibitor) and voglibose (an α-glucosidase inhibitor) monotherapy in Japanese patients with type 2 diabetes who have inadequate glycaemic control (HbA1c ≥6.5% and <10.0%) on diet and exercise. Methods:In a multi-center, randomized, double-blind, parallel-group study, 319 patients were randomized (1:1) to 12-week treatment with sitagliptin 50 mg once daily or voglibose 0.2 mg thrice daily before meals. The primary analysis ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
69
2
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 25 publications
19
69
2
1
Order By: Relevance
“…1A). The AUCs of the plasma glucose levels in the M, S and M+S groups were treatment in Japanese patients with type 2 diabetes [16]. Of note, sitagliptin, unlike miglitol, failed to decrease the plasma glucose levels at 30 min after the start of breakfast (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…1A). The AUCs of the plasma glucose levels in the M, S and M+S groups were treatment in Japanese patients with type 2 diabetes [16]. Of note, sitagliptin, unlike miglitol, failed to decrease the plasma glucose levels at 30 min after the start of breakfast (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Low-density lipoprotein cholesterol levels were calculated by the Friedewald equation because all patients had TG levels less than 400 mg/dL [15]. Serum apolipoprotein AI, apolipoprotein AII, ApoB, apolipoprotein CII, apolipoprotein CIII, and apolipoprotein E levels were determined using turbidimetric immunoassays (Apo A-I Auto N "Daiichi," Apo A-II Auto N the total caloric content was approximately 500 kcal, with 75 g carbohydrate and 18.8 g protein [9].…”
Section: Measurementsmentioning
confidence: 99%
“…Simple randomization was performed in order of clinic visits using a random number table. Based on previous reports that showed a 12-week post-interventional decrease of 0.70% in hemoglobin A 1c (HbA 1c ) with sitagliptin [9] and of 0.16% in HbA 1c with miglitol [11], the sample size was estimated to be approximately 15 in each group with a significance level (α) of 5% and detection level (1 − β) of 80% (2-tailed). Eligibility criteria were as follows: age > 20 years, the absence of pregnancy, fasting serum triglyceride (TG) levels < 250 mg/dL, HbA 1c < 9.4%, serum creatinine level < 1.0 mg/dL, and no changes in medications during the 3 months before enrollment in the study.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2009, the dipeptidyl peptidase-4 (DPP-4) inhibitor sitagliptin was approved as the first incretin enhancer for use in Japan [4][5][6][7][8][9][10][11] . Although it has been suggested that seasonal fluctuations of hemoglobin A1c (HbA1c) are noted in patients with type 2 diabetes, no reports have been published concerning the efficacy of antidiabetic agents for such fluctuations.…”
Section: Introductionmentioning
confidence: 99%